Survival Analysis of Multi-Drug Resistant Tuberculosis Patients in North Sumatra - Dessritina, Pesona; Nursal, Dien Gusta Aggraini; Syafrawati, Syafrawati (Jurnal Kesehatan - STIKes Prima Nusantara, 2023)
Background: The severity and ease of spread of MDR-TB have caused this disease to become an epidemic in various countries. WHO has also launched an international program "End TB" which until now has not even reached half of the target. Indonesia is already in the third highest position after India and China with a CFR of 0.11% and North Sumatra Province is already at the 6th highest level in Indonesia and the highest on the island of Sumatra.Purpose : The purpose of this study was to see the survival of MDR-TB patients in North Sumatra Province.Methods: The method in this study used a retrospective cohort design with secondary data on MDR-TB cases for 2020 – 2022. The sample used was total sampling with the condition that it met the sample criteria, namely complete data and treatment results. The analysis was carried out using univariate, Kaplan-Meier, bivariate analysis using the logrank test and multivariate with full model logistic regression.Results: The results obtained from a total of 664 cases (26.81%) died and (73.19%) survived. The variables related to survival in MDR-TB patients were age (p = 0.000 HR (Hazard Ratio) 1.88) and HIV status (p = 0.001 HR 1.40). The dominant variable related to survival is age (p = 0.000 HR 0.64).Conclusion: based on statistical tests, age and HIV status had a significant relationship with survival, while gender, OAT resistance, history of DM, history of treatment and treatment delays had no significant relationship based on statistical tests in this study.